Optimizing the Management of Cancer Patients Treated With Systemic Therapies During the COVID-19 Pandemic: The New Role of PCR and CT Scan - Viansone, Alessandro A.; Ammari, Samy; Dercle, Laurent; Arnedos, Monica (Frontiers in Oncology, 2021)
In late 2019 and early 2020, the world witnessed the outbreak of the SARS-CoV-2 (also referred as COVID-19) in Wuhan, China. Its rapid expansion worldwide and its contagiousness rate have forced the activation of several measures to contain the pandemic, mostly through confinement and identification of infected patients and potential contacts by testing. Initial advice from the Chinese series of COVID-19 in cancer patients suggested that postponing adjuvant chemotherapy or elective surgery for less aggressive cancers should be considered and that the increased risk for personal protection should be emphasized for patients with cancer or cancer survivors. Furthermore, more intensive surveillance or treatment should be considered for those patients with cancer who are infected with SARS-CoV-2. These measures have been later taken by healthcare organizations like ASCO and ESMO. Systematic reports about the prevalence of cancer in patients with COVID-19 and the real incidence of COVID-19 infection among cancer patients are starting to be made public. The standard method to diagnose infection by COVID-19 is through identification by RT-PCR SARS-CoV-2 testing. Several strategies are available in order to increase sensitivity and specificity of this testing as the realization of chest CT scans in patients suspected or tested for Covis-19 in addition to RT-PCR for nasal or oropharynx swabs. Despite the standardized use of CT scans in addition (or instead of) RT-PCR for the diagnoses of a suspected COVID-19 infection might still be controversial.